(untitled) (Pedagogy of Higher and Secondary Education, 2011)
Two levels of intellectual and emotional development of students in learning of the theoretical foundational Physics learning were revelated. Trends of efficiency of intellectual and emotional development of pupilsin learning of Rhysics were analyzed.